Safety, Pharmacokinetics, and Antiviral Activity of AT-527, a Novel Purine Nucleotide Prodrug, in Hepatitis C Virus-Infected Subjects with or without Cirrhosis - Berliba, Elina; Bogus, Maxim; Vanhoutte, Frédéric; Berghmans, Pieter-Jan; Good, Steven S.; Moussa, Adel; Pietropaolo, Keith; Murphy, Robert L.; Zhou, Xiao-Jian; Sommadossi, Jean-Pierre (Antimicrobial agents and chemotherapy, 2019)
AT-527 is a novel modified guanosine nucleotide prodrug inhibitor of the hepatitis C virus (HCV) NS5B polymerase, with increased in vitro antiviral activity compared to sofosbuvir and a highly differentiated favorable preclinical profile compared to other anti-HCV nucleoside/nucleotide analogs. AT-527 is a novel modified guanosine nucleotide prodrug inhibitor of the hepatitis C virus (HCV) NS5B polymerase, with increased in vitro antiviral activity compared to sofosbuvir and a highly differentiated favorable preclinical profile compared to other anti-HCV nucleoside/nucleotide analogs. This was a multiple-part clinical study where multiple ascending doses of AT-527 up to 600 mg (expressed as AT-527 salt form; equivalent to 553 mg free base) once daily for 7 days were evaluated in a randomized, double-blind, placebo-controlled study of treatment-naive, noncirrhotic, genotype 1b, HCV-infected subjects. The highest dose of AT-527 for the same duration was then evaluated in two open-label cohorts of (i) noncirrhotic, genotype 3, HCV-infected subjects and (ii) HCV-infected subjects of any genotype with compensated (Child-Pugh A) cirrhosis. AT-527 was well tolerated for 7 days in all cohorts. At the highest dose tested, mean HCV RNA reductions of up to 2.4 log 10 IU/ml occurred within the first 24 h of dosing. Mean maximum reductions observed with 7 days of dosing were 4.4, 4.5, and 4.6 log 10 IU/ml in noncirrhotic subjects with HCV genotype 1b, noncirrhotic subjects with HCV genotype 3, and subjects with compensated cirrhosis, respectively. The systemic half-life of AT-273, the nucleoside metabolite considered a surrogate of intracellular phosphates including the active triphosphate, exceeded 20 h, supporting once-daily dosing. In summary, AT-527 demonstrated rapid, potent, dose/exposure-related, and pangenotypic antiviral activity with similar responses between subjects with and without cirrhosis. Exposure-antiviral response analysis identified 550 mg (free base equivalent) as the optimal dose of AT-527. Safety and antiviral activity data from this study warrant continued clinical development of AT-527 dosed once daily. (This study has been registered in the European Union Drug Regulating Authorities Clinical Trials Database [EudraCT] under number 2017-002148-34 and at ClinicalTrials.gov under identifier NCT03219957.)